2016
DOI: 10.1002/2016ja022588
|View full text |Cite
|
Sign up to set email alerts
|

Current energetic particle sensors

Abstract: Several energetic particle sensors designed to make measurements in the current decade are described and their technology and capabilities discussed and demonstrated. Most of these instruments are already on orbit or approaching launch. These include the Magnetic Electron Ion Spectrometers (MagEIS) and the Relativistic Electron Proton Telescope (REPT) that are flying on the Van Allen Probes, the Fly's Eye Electron Proton Spectrometers (FEEPS) flying on the Magnetospheric Multiscale (MMS) mission, and Dosimeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The observation of pitch-angle distribution from the Van Allen Probes suggested that high-energy protons around 26.0 MeV concentrate near the magnetic equator [2]. Particle measurement of the Van Allen Probes has a gap of proton energies between 1 and 17 MeV [3] and thus we cannot make a direct comparison with our results of >6.0 MeV protons. However, observation results of the International Journal of Astronomy and Astrophysics Van Allen Probes were obtained at 26.0, 46.0, and 66.0 MeV, and a greater concentration near the equator was found for lower energies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The observation of pitch-angle distribution from the Van Allen Probes suggested that high-energy protons around 26.0 MeV concentrate near the magnetic equator [2]. Particle measurement of the Van Allen Probes has a gap of proton energies between 1 and 17 MeV [3] and thus we cannot make a direct comparison with our results of >6.0 MeV protons. However, observation results of the International Journal of Astronomy and Astrophysics Van Allen Probes were obtained at 26.0, 46.0, and 66.0 MeV, and a greater concentration near the equator was found for lower energies.…”
Section: Discussionmentioning
confidence: 65%
“…They are revealed for protons with energies greater than 18 MeV. Since proton measurement with the Van Allen Probes has a gap of proton energies between 1 and 17 MeV [3], properties of several to ten MeV protons have not been studied.…”
mentioning
confidence: 99%
“…Finally, in addition, FIREBIRD observations along with related measurements have been used to quantify the effects of electron precipitation on chemistry of the middle atmosphere (Duderstadt et al, 2021;Seppälä et al, 2018), another important consequence of space weather to the neighboring field of atmospheric science. There is broad agreement that low-resource CubeSat missions at low altitude such as FIREBIRD-II and CSSWE and others not described in this paper, such as AC6 , have advanced the science associated with energetic charged particles in Earth's magnetosphere (e.g., Fennell et al, 2016).…”
Section: Firebird-ii Science Achievementsmentioning
confidence: 58%
“…The last column of Table 1 includes a reference for each instrument. The Magnetic Electron Ion Spectrometer (MagEIS), Relativistic Electron Proton Telescope (REPT), and Fly's Eye Energetic Particle Spectrometer (FEEPS) instruments are also compared and reviewed thoroughly by Fennell et al (2016).…”
Section: Previous Observationsmentioning
confidence: 99%